Voces en un campo de sangre: Max Aub y los penúltimos episodios nacionales - Oleza Simó, Joan (Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación, 2002)
Certain reading of postmodernity has diagnosed (actually, offered) the end of history, and therefore the end of historical novel, although some of us choose not to bury it but to bring it to live again. Within the context of this debate it is worth to stop at Max Aub's Laberinto mágico, which is a Spanish Civil War magnificent mural as well as one of the last manifestation of the pure model of national episode, Galdós and Valle Inclán's ultimate legacy. In spite of containing apparent heterogeneous elements, the historical and ideological signs in Campo cerrado (1939) are the ones of modern historical novel. In the following campos, Aub's historical-novel formula reached its maturity, Campo del moro (1963) possibly being the most brilliant and balanced example in this modality among the novels of the series. In it, the of history announced in, Campo del moro banishes away as a victim of treason and shocked by the madness that grows on Madrid's streets. Campo del moro could be considered a pure historical novel, since the necessary felicity conditions are accomplished, causing this genre to be completely fulfilled: historicity of the events and respect for the chronological order in which they occur; fiction limited by the historical referent; initiative of the historical events over fiction, and power of the public logic over the private; and last but not least, narrativity of the events manifestated in the selection of the golpe de estado of Casado and Besteiro and their enlightment as the key to the historical story. Three are the big issues that are presented in the argumental logic of the novel: treason, the confusion in the maze and the heroic cause degradation. ln Max Aub's speech, which feeds the novel, fiction, reality and history are weaved together to the point of creating Ariadna's in the Maze.